Socio-environmental Impact of Research - Cardoso Ventura, Andréa (2021)
Reflecting about the future of Earth and its inhabitants is essential to ensure a possible tomorrow. Therefore, socio-environmental impact shall become a universal and inevitable concern of researchers, educational institutions and scientific research regulatory agencies. Social and environmental impacts, in all senses, must be considered into any production of knowledge. Some questions help incorporate this conduct in academic research: How can research ensure effective socio-environmental impacts on society? What is the best way to conduct research so that it has positive social and environmental impacts from the beginning? How can research be fully dedicated to generating positive socio-environmental impacts in every step? We concluded that socio-environmental impacts must be considered just as much or even more important than those of socioeconomic and technological nature.